Nutrition knowledge, food insecurity and coping strategies amongst Health Care Science students at the University of Limpopo - Mashabela, Mohube Elizabeth (My University, 2023)
Introduction: Nutritional knowledge is essential for selecting healthy and nutritious meals. However, access to consistent, adequate and nutritious food was unattainable for university students, despite the fact that food was considered a human basic right. Food insecurity is a real issue in South African universities, but it is poorly documented. Numerous studies have used one approach to measure food insecurity rates in various universities, either quantitative or qualitative. There is a scarcity of data on food insecurity among students in institutions of higher learning in Limpopo Province. Food insecure students used a variety of coping mechanisms such as, borrowing money, buying cheap food, skipping meals, sharing food, and reducing portion size in order to cope with food insecurity. The goal of the study was to investigate the level of nutrition knowledge, food insecurity, and coping strategies among students at the School of Health Care Sciences. at the University of Limpopo, South Africa. Methodology: The explanatory sequential mixed-method approach was used in this study. The quantitative survey employed convenience sampling, with 237 undergraduate participants from the Health Care Sciences. Nutritional knowledge was assessed using a multiple-choice questionnaire adapted from the Perlstein study. Food security status was assessed using the eight (8) questions from Food Insecurity Experience Scale. Fourteen purposefully selected in-depth qualitative interviews were conducted to explore life experiences and coping strategies of food-insecure students. Statistical analysis was performed using STATA version 11.0, Fischer’s exact test to test the association between food insecurity and nutritional knowledge with regards to age, gender and study level and thematic analysis for the qualitative data. Findings: Students were on average 21 years old, in level II and level III years of study. Fifteen percent (n=36) had poor nutritional knowledge, 69% (n=164) had moderate nutrition knowledge, and 14.7% (n=35) had good nutritional knowledge. Both males and females in the current study had a fair amount of dietary knowledge. Twenty-four percent (n=57) experienced moderate food insecurity and 16% (n=37) had severe food insecurity. The rate of food insecurity in the study exceeded the national rate. Lack of budgeting skills, delayed distribution of bursary money, unforeseen costs, and household obligations were among the factors that aided in food insecurity. Food-insecure students applied numerous coping mechanisms, such as borrowing money from friends, sharing food, buying cheap food, and cutting portion sizes. The study found a significant association between a study level and nutrition knowledge with a P-value of 0.02 for both study levels less than and more than two years. Six themes emerged from interviews with food-insecure students i.e., coping strategies, nutrition knowledge, hunger and academic effect, competing expenses, health triangle and contributing factors to lack of money to buy food. Conclusion: This study provided insight into the food insecurity levels and the nutritional knowledge of the students in the Health Care Sciences at the University of Limpopo. It further offered an understanding of how students experienced food insecurity and the various coping mechanisms employed to deal with the situation. The rate of food insecurity in the study exceeded the national rate. Nutrition education programmes and interventions that address food insecurity are important and the strengthening of existing support systems to ensure that students cope and succeed in their studies. Future research is needed to cover a large scale of students.
Thesis (M.Sc. (Dietetics)) -- University of Limpopo, 2023
Keywords: Food in/security; Students; Coping strategies; Nutrition knowledge; Nutrition; Food security -- South Africa -- Limpopo; College students -- South Africa -- Limpopo